Root hydraulic conductance, aquaporins and plant growth promoting microorganisms: A revision - Groppa, María Daniela (2012)
A considerable number of soil and rhizospheric fungi and bacteria collectively known as plant growth promoting microorganisms (PGPM) have demonstrated ability to colonize plant roots and to provide benefits to their hosts. Among these benefits, many authors documented improved root hydraulic conductance and alleviation of abiotic stresses such as drought and salinity. Today, it is accepted that movement through aquaporins represents a quite faster pathway of water movement across biological membranes. This review is intended to reflect the state of art in the knowledge of PGPM effects on plant water status and root hydraulic conductance, with special emphasis on the experimental data that prove or suggest an impact of PGPM on root aquaporins under both normal and water limiting conditions.